Biocompatible chitosan-based composites with properties suitable for hyperthermia therapy. Issue 6 (21st January 2020) - Barra, Ana; Alves, Zélia; Ferreira, Nuno M.; Martins, Manuel A.; Oliveira, Helena; Ferreira, Liliana P.; Cruz, M. Margarida; Carvalho, Maria de Deus; Neumayer, Sabine M.; Rodriguez, Brian J.; Nunes, Cláudia; Ferreira, Paula
Abstract : Sustainably made, flexible and biocompatible composites, having environmentally friendly compositions and multifunctional capabilities, are promising materials for several emerging biomedical applications. Abstract : Sustainably made, flexible and biocompatible composites, having environmentally friendly compositions and multifunctional capabilities, are promising materials for several emerging biomedical applications. Here, the development of flexible and multifunctional chitosan-based bionanocomposites with a mixed reduced graphene oxide-iron oxide (rGO-Fe3− x O4 ) filler is described. The filler is prepared by one-pot synthesis, ensuring good dispersibility of the Fe3− x O4 nanoparticles and rGO within the chitosan matrix during solvent casting. The resulting bionanocomposites present superparamagnetic response at room temperature. The antioxidant activity is 9 times higher than that of pristine chitosan. The mechanical properties of the films can be tuned from elastic (∼8 MPa) chitosan films to stiff (∼285 MPa) bionanocomposite films with 50% filler. The magnetic hyperthermia tests showed a temperature increase of 40 °C in 45 s for the 50% rGO-Fe3− x O4 film. Furthermore, the composites have no cytotoxicity to the nontumorigenic (HaCat) cell line, which confirms their biocompatibility and highlights the potential of these materials for biomedical applications, such as hyperthermia treatments.